The Effect of Unilateral Load Carriage on the Muscle Activities of the Trunk and Lower Limbs of Young Healthy Males during Gait - Corrigan, Liam (Université d'Ottawa / University of Ottawa, 2012)
The aim of the study was to examine the muscle activities of fifteen male participants (23.44 ±2.63 years) during unilateral hockey bag load carrying of different weights (10%, 20%, and 30% bodyweight) and sizes (small and large). Walking without a hockey bag was the control condition. The results showed that increased peak and integrated EMG occurred with an increased load weight in the semitendinosus, gastrocnemius, rectus abdominis, and vastus medialis. The left rectus femoris and left semitendinosus were both significantly greater than the right corresponding muscle. Carrying the large hockey bag produced greater peak EMG in the right rectus abdominis and the right rectus femoris, whereas the right vastus medialis showed a larger peak EMG in the small hockey bag. It was concluded that the posterior-lateral carrying style of hockey bag load carriage explained the results being similar to both backpack and side pack load carriage studies.
Keywords: unilateral load carriage; electromyography; hockey bag